Case Report: Drug-induced pneumonia caused by moxifloxacin and a literature review - Gao, Zhan; Jiang, Yunqiu; Zhang, Mingzhou; Luo, Chenjing; Wei, Zhenghua; Gong, Daohui; Wang, Guansong (Frontiers in Medicine, 2025)
Drug-induced pneumonia is a rare and potentially life-threatening adverse drug reaction. Moxifloxacin is a fluoroquinolone antibiotic with broad-spectrum antimicrobial activity. Despite reports of moxifloxacin-related side effects such as interstitial nephritis, recurrent tendinitis, and pseudoallergic reactions, moxifloxacin-induced pneumonia is exceedingly rare. We report the case of a 45-year-old male who developed fever and cough, and progressed to hypersensitivity syndrome related to drug-induced pneumonia following moxifloxacin therapy. Discontinuation of moxifloxacin led to resolution of fever with significant resolution of pulmonary lesions. Comprehensive laboratory investigations ruled out other causes, confirming drug-induced pneumonia due to moxifloxacin. This case report provides typical clinical manifestations and pulmonary imaging changes, as well as an analysis of differential diagnosis of pulmonary lesions and key management strategies. The case and related literature review contribute to enhancing our understanding of moxifloxacin-related pneumonia, with important clinical significance in promptly correcting adverse reactions and improving patient outcomes.